Upper Cervical Compression Myelopathy Caused by the Retro-Odontoid Pseudotumor With Degenerative Osteoarthritis and Calcium Pyrophosphate Dihydrate Disease: A Case Report and Literature Review - Takashi Yurube; Tetsuhiro Iguchi; Keisuke Kinoshita; Takashi Sadamitsu; Kenichiro Kakutani (Neurospine, 2021)
The retro-odontoid pseudotumor is often concurrent with atlantoaxial subluxation (AAS). Therefore, the pseudotumor is relatively common in rheumatoid arthritis (RA) but rare in primary osteoarthritis (OA). This is a case report of an elderly male patient suffering from neck pain and compression myelopathy caused by the craniocervical pseudotumor with OA but without atlantoaxial instability. He had long-lasting peripheral and spinal pain treated by nonsteroidal anti-inflammatory drugs. Imaging found upper cervical spondylosis without AAS or dynamic instability but with periodontoid calcifications and ossifications, suggesting calcium pyrophosphate dihydrate (CPPD) crystal deposition. Based on a comprehensive literature search and review, CPPD disease around the atlantodental joint is a possible contributor to secondary OA development and retro-odontoid pannus formation through chronic inflammation, which can be enough severe to induce compression myelopathy in non-RA patients without AAS. The global increase in the aged population advises caution regarding more prevalent upper cervical spine disorders associated with OA and CPPD.